2023
DOI: 10.31004/joe.v6i1.3262
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Karakter Komunikatif dan Disiplin melalui Metode Culturally Responsive Teaching dengan Pembelajaran Sosial Emosional pada Pembelajaran Sejarah Siswa Kelas X-2 SMAN 1 Kalitidu

Abstract: The learning process often only focuses on the academic results achieved and tends to ignore the ability of character skills in students, one of which is communicative and disciplined character. This research aims to get an overview of the implementation of the culturally responsive teaching approach with social-emotional learning in history learning for class X-2 students of SMAN 1 Kalitidu. The data obtained from this study were in the form of communicative and disciplined characters in students in learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous research indicates that the Culturally Responsive Teaching approach in education can stimulate learner participation and enhance their engagement in the learning process (Maryono et al, 2021). The research conducted by Nasution et al (2023) successfully demonstrated that the Culturally Responsive Teaching approach with social-emotional learning can enhance learners' communicative character and discipline. The Culturally Responsive Teaching approach can also improve the scientific literacy of learners (Salma et al, 2023).…”
Section: Introductionmentioning
confidence: 94%
“…Previous research indicates that the Culturally Responsive Teaching approach in education can stimulate learner participation and enhance their engagement in the learning process (Maryono et al, 2021). The research conducted by Nasution et al (2023) successfully demonstrated that the Culturally Responsive Teaching approach with social-emotional learning can enhance learners' communicative character and discipline. The Culturally Responsive Teaching approach can also improve the scientific literacy of learners (Salma et al, 2023).…”
Section: Introductionmentioning
confidence: 94%